AUTONOMIC HEART RATE MODULATION AND FUNCTIONAL AEROBIC CAPACITY IN HEMIPARETIC PATIENTS - Campos, Monica Furquim de [UNESP]; Vieira, Suenimeire; Pepe Ambrozin, Alexandre Ricardo [UNESP]; Catai, Aparecida Maria; Quiterio, Robison Jose [UNESP] (Soc Brasileira Med Esporte, 2016)
Introduction: It has been observed that individuals affected by stroke have, in addition to the physical damage, decreased aerobic capacity and impaired heart rate variability, which are important factors for the onset of cardiac diseases and arrhythmias. Objective: To investigate the chronic effects of stroke on aerobic capacity (VO2peak) and the indices of heart rate variability (HRV), and if there is a correlation between these two variables. Methods: Eleven male individuals aged 55 to 65 affected by cerebrovascular injury for at least six months all with hemiparesis were assessed. The following evaluations were performed: maximum aerobic capacity test, record of R-R intervals and calculation of the indices of HRV (RMSSD, pNN50, HF, LF and LF/HF ratio). For the comparison between expected and obtained VO2peak the unpaired Student's t-test was used. To test the hypothesis of correlation between HRV indices and VO2peak the Pearson correlation test was used. Results: VO2peak (mL. kg(1). min(1)) expected and obtained, respectively = 32.15 +/- 1.87 and 16.12 +/- 5.51; HRV indices: RMSSD (ms) = 28.69 +/- 26.78; pNN50 (%) = 8.76 +/- 2.62; HF (n. u.) = 51.96 +/- 22.4; LF (n. u.) = 48.04 +/- 22.49. The VO2peak correlated negatively with the RMSSD, pNN50 and HF indices; and positively with LF (p< 0.05). Conclusion: In the chronic phase of stroke, the heart rate variability is normal and individuals with lower aerobic capacity have higher parasympathetic modulation and lower sympathetic modulations, probably due to the higher physical demand on physical activities of daily living.
Keywords: stroke; heart rate; oxygen consumption; autonomic nervous system